2017
DOI: 10.1177/1010428317702548
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits bladder cancer progression via regulation of β-catenin expression

Abstract: Bladder cancer has a considerable morbidity and mortality impact with particularly poor prognosis. Curcumin has been recently noticed as a polyphenolic compound separated from turmeric to regulate tumor progression. However, the precise molecular mechanism by which curcumin inhibits the invasion and metastasis of bladder cancer cells is not fully elucidated. In this study, we investigate the effect of curcumin on the bladder cancer as well as possible mechanisms of curcumin. The expression of β-catenin was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…The common treatment for bladder cancer focuses on radical cystectomy, but most patients experience relapse after excision (14). Because of this, adjuvant chemotherapy is usually performed in an effort to delay recurrence and prolong survival (14,15). However, there are reported that adjuvant chemotherapy responded to 50% of muscle-invasive bladder cancer patients (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The common treatment for bladder cancer focuses on radical cystectomy, but most patients experience relapse after excision (14). Because of this, adjuvant chemotherapy is usually performed in an effort to delay recurrence and prolong survival (14,15). However, there are reported that adjuvant chemotherapy responded to 50% of muscle-invasive bladder cancer patients (15,16).…”
mentioning
confidence: 99%
“…Because of this, adjuvant chemotherapy is usually performed in an effort to delay recurrence and prolong survival (14,15). However, there are reported that adjuvant chemotherapy responded to 50% of muscle-invasive bladder cancer patients (15,16). Therefore, there is a need to develop a novel treatment strategies for the overcome these challenges of bladder cancer.…”
mentioning
confidence: 99%
“…Several studies have confirmed the ability of curcuminoid members to suppress cancer cell migration and invasion. For example, curcumin inhibits migrated cells from entering into the wound area of lung [28], breast [29], and bladder [30] cancer cells, while DMC inhibits the motility of breast [31] and prostate [32] cancer cells. Further, BDMC inhibits the migration of ovarian [33] and lung [34] cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…While curcuminoids are composed of three main members-curcumin, DMC, and BDMC-all have shown efficient anticancer effects against various malignancies and induce apoptosis, but with different potencies. Although many studies present curcumin as the active ingredient in turmeric, with a strong ability to kill different cancer cells such as hepatic [37], lung [28], breast [38], pancreas [27], bladder [30], and ovarian [39] cancer cells, DMC, which is more stable than curcumin, was reported by Simon et al [40] to exhibit the strongest antitumor activity among the three curcuminoids against breast cancer cells. DMC has also shown ability to inhibit the growth of prostate cancer cells [32].…”
Section: Discussionmentioning
confidence: 99%
“…The present study focused on curcumin, as a natural polyphenol isolated from the spice turmeric (26). Previous studies have demonstrated that curcumin suppresses cytotoxicity and DNA injury by suppressing oxidative damage caused by reactive oxygen species (27,28).…”
Section: Discussionmentioning
confidence: 99%